Cardiac malformations, adrenal agenesis, neural crest defects and exencephaly in mice lacking Cited2, a new Tfap2 co-activator. - Bamforth, S; Bragança, J; Eloranta, J; Murdoch, J; Marques, F; Kranc, K; Farza, H; Henderson, D; Hurst, H; Bhattacharya, S (2001)
The protein EP300 and its paralog CREBBP (CREB-binding protein) are ubiquitously expressed transcriptional co-activators and histone acetyl transferases. The gene EP300 is essential for normal cardiac and neural development, whereas CREBBP is essential for neurulation, hematopoietic differentiation, angiogenesis and skeletal and cardiac development. Mutations in CREBBP cause Rubinstein-Taybi syndrome, which is characterized by mental retardation, skeletal abnormalities and congenital cardiac defects. The CBP/p300-interacting transactivator with ED-rich tail 2 (CITED2) binds EP300 and CREBBP with high affinity and regulates gene transcription. Here we show that Cited2-/- embryos die with cardiac malformations, adrenal agenesis, abnormal cranial ganglia and exencephaly. The cardiac defects include atrial and ventricular septal defects, overriding aorta, double-outlet right ventricle, persistent truncus arteriosus and right-sided aortic arches. We find increased apoptosis in the midbrain region and a marked reduction in ErbB3-expressing neural crest cells in mid-embryogenesis. We show that CITED2 interacts with and co-activates all isoforms of transcription factor AP-2 (TFAP2). Transactivation by TFAP2 isoforms is defective in Cited2-/- embryonic fibroblasts and is rescued by ectopically expressed CITED2. As certain Tfap2 isoforms are essential in neural crest, neural tube and cardiac development, we propose that abnormal embryogenesis in mice lacking Cited2 results, at least in part, from its role as a Tfap2 co-activator.